2010
DOI: 10.1021/bi901900s
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Flow of Water through Photosystem II Using Molecular Dynamics and Streamline Tracing

Abstract: The CaMn(4) cluster of the oxygen-evolving complex (OEC) of photosynthesis catalyzes the light-driven splitting of water into molecular oxygen, protons, and electrons. The OEC is buried within photosystem II (PSII), a multisubunit integral membrane protein complex, and water must find its way to the CaMn(4) cluster by moving through protein. Channels for water entrance, and proton and oxygen exit, have previously been proposed following the analysis of cavities found within X-ray structures of PSII. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 50 publications
1
79
0
Order By: Relevance
“…This channel has been shown via molecular dynamics to be impermeable to water [11], with a barrier of $22 kcal/mol at the bottleneck composed of D1-L91, CP43-F292, and CP43-F358 [12 ]. This leaves the 'narrow,' 'broad,' and 'large' channel systems as options for water entry from the lumen to the OEC ( Figure 2, with nomenclature from [9,13,14]).…”
Section: Introductionmentioning
confidence: 99%
“…This channel has been shown via molecular dynamics to be impermeable to water [11], with a barrier of $22 kcal/mol at the bottleneck composed of D1-L91, CP43-F292, and CP43-F358 [12 ]. This leaves the 'narrow,' 'broad,' and 'large' channel systems as options for water entry from the lumen to the OEC ( Figure 2, with nomenclature from [9,13,14]).…”
Section: Introductionmentioning
confidence: 99%
“…Gabdulkhakov et al (24) additionally performed Xe gas co-crystallization x-ray crystallography. Recently, molecular dynamic simulations coupled with water streamline tracing have been used to map the path of water movement to the oxygen-evolving site (25,26). These authors identified five putative water channels which, in large measure, are similar to the channels identified in previous studies (see Table 1,Ref.…”
Section: Discussionmentioning
confidence: 74%
“…Briefly, since most of the computational studies examine static crystal structures (22,24,41), they fail to take into account molecular motion on the nsec time scales which could substantially alter the overall shape and dimensions of the identified water channels within PS II. Vassiliev et al (25,26) have at least partially addressed this problem using molecular dynamic simulations of water movement within the photosystem. It has also been implicitly assumed that no conformational changes occur in the PS II structure during normal S-state cycling which affect either water transport to the active site (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the current crystal structure identified a third chloride ion bound near the C-terminal amino acid of PsbU, which is located between PsbU and cytochrome c 550 Kawakami et al, 2011). This chloride is ligated by water molecules and lies close to the exit of a proposed hydrogen-bonding network leading from the Mn 4 CaO 5 cluster to the lumen that could possibly serve to transport anions, water or protons (Gabdulkhakov et al, 2009;Vassiliev et al, 2010;Kawakami et al, 2011 …”
Section: Role Of Chloride In Oxygen Evolutionmentioning
confidence: 81%